2023
DOI: 10.3390/toxics11090769
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure Assessment and Its Impact on the Structural Organization and Morphological Peculiarities of Rat Ovaries

Adam Osowski,
Larysa Fedoniuk,
Yaroslav Bilyk
et al.

Abstract: Lead is known to be highly toxic to humans, causing various disorders infetal development. An experiment was conducted to examine the effects of lead acetate on the structural organization of female rat ovaries. The study involved 40 non-linear female rats divided into four groups: a control group, a low-dose group, a moderate-dose group, and a high-dose group. The rats were given lead acetate solutions in varying doses for 30 days, and their ovarian tissue was examined using light microscopy.The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(105 reference statements)
2
0
0
Order By: Relevance
“…Treatment with ASFE following lead acetate intoxication led to a significant improvement in the % b. wt of rats. These findings agreed with previous investigations reporting weight loss and reduced intestinal absorption upon exposure to lead in experimental animals [51]. A previous study reported the improvement of body weight loss in rats that was induced by lead upon treatment with natural products.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Treatment with ASFE following lead acetate intoxication led to a significant improvement in the % b. wt of rats. These findings agreed with previous investigations reporting weight loss and reduced intestinal absorption upon exposure to lead in experimental animals [51]. A previous study reported the improvement of body weight loss in rats that was induced by lead upon treatment with natural products.…”
Section: Discussionsupporting
confidence: 93%
“…Adeyi et al (2023) investigated the beneficial role of ferulic acid as an anti-inflammatory agent via the modulation of SOCS-1 signaling pathways in testicular inflammation in a rat model [66]. Lead acetate exposure caused significant histopathological alterations in the testis architectures that were consistent with previous studies [51,56,72]. However, in this investigation, treatment with ASFE for lead acetate intoxication improved sperm characteristics significantly and affirmed the normal histological structure of most seminiferous tubules.…”
Section: Discussionsupporting
confidence: 85%